Protein-energy malnutrition (PEM) and protein catabolism with progressive liver cirrhosis - Dichi, J. B. [UNESP]; Papini-Berto, S. J. [UNESP]; Angelelli, A. Y.O. [UNESP]; Bicudo, M. H. [UNESP]; Dichi, I. [UNESP]; Rezende, T. A. [UNESP]; Burini, R. C. [UNESP] (My University, 1997)
The occurrence of protein hypercatabolism state with the progressing of liver impairment was investigated in male, adult cirrhotic patients under the conditions of fasting (DO) and feeding either normal-protein (D1, D2 = 0.9 g protein/kg/day) and high-protein (D3, D4 = 1.6 g protein/kg/day) with either normal-energy (D1, D3 = 37 kcal/kg/day) and high-energy (D2, D4 = 46 kcal/kg/day) diets during 3 days each. The subjects were grouped according to their liver failure degree (Child-Turcotte-Pugh) in healthy control (G1, n = 4), Child A (G2, n = 5) and Child B + C (G3, n = 6) groups. The progressive impairment of the liver was associated with increasing levels of plasma bilirrubin and γGT activity and decreased values of hematocrit, hemoglobin and lymphocytes. All patients presented some degree of PEM which followed the liver failure scale. The anthropometric protein/energy stores differentiated the control/patient groups whereas the plasma albumin (G3 < others) and transthyretin (G1 > G2 > G3) discriminated the patient groups. The 15N-glycine study evidenced the Child A patients (G2) as normometabolic under hypo-hyper protein/energy diets whereas the G3 group was hypermetabolic. The higher N-retention of Child A (G2) was under high protein-normal energy diet (D3) whereas for G3 it happened under high protein/high-energy diet (D4). Thus the progressive degree of liver cirrhosis is accompanied by increasing degree of PEM detectable through sensitive PEM markers. Child A PEM seems coexistent with protein normometabolism status very responsive to high-protein/normal energy diet whereas the protein hypermetabolic status of the Child B + C besides maintained presents better nitrogen retaining under high-protein/high energy diet.